Fruit abscission and stem browning on table grapes - Ferreira, Maria Aparecida Rodrigues; Nassur, Rita de Cássia Mirela Resende; Hausen, Leandro José Oliveira de Von; Souza, Flávio de França; Freitas, Sérgio Tonetto de (Comunicata Scientiae, 2017)
Most of the postharvest losses on table grapes are related to the berry abscission and stem browning that affect the product appearance, reducing its commercial value and becoming a problem to table grapes production chain worldwide. The aim of this study was to evaluate the effect of pre-harvest application of foliar fertilizers, plant growth regulators or a mix of both on table grapes var. ‘Sweet Globe’ quality parameters. All treatments were applied in a volume of 100 L ha-1 after 75 days (pre-softening), 95 days (ten days before harvest) and 103 days (two days before harvest). The clusters were harvested at the commercial harvest maturity stage, packed and stored in a cold room (0 °C and 95% RH), being evaluated for berry abscission, stem browning, firmness, abscission force, soluble solids, acidity, stem dry matter, stem water activity and weight loss at harvest and at 14, 42 and 56 days of storage. Although there was no statistical difference from control, the pre-harvest application of Hold® + Gibberellin resulted in clusters with lower percentage of berry abscission and the application of Kamab® resulted in clusters with lower stem browning, both evaluated after 56 days of storage.